Direct Oral Anticoagulants vs. Warfarin in Latin American Patients With Atrial Fibrillation: Evidence From Four post-hoc Analyses of Randomized Clinical Trials - Liu, Fuwei; Wang, Yunhong; Luo, Jun; Huang, Lin; Zhu, Wengen; Yin, Kang; Xue, Zhengbiao (Frontiers in Cardiovascular Medicine, 2022)
Background: Several studies have investigated the effect of direct oral anticoagulants (DOACs) in Latin American patients with atrial fibrillation (AF), but the results remain controversial. Therefore, we aimed to compare the efficacy and safety of DOACs versus warfarin in Latin American patients with AF. Methods: We systematically searched the PubMed and Embase databases until November 2021 for studies that compared the effect of DOACs versus warfarin in Latin patients with AF. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled by a random-effects model using an inverse variance method. Results: Four post hoc analyses of randomized clinical trials (RCTs) involving 42,411 DOACs and 29,270 warfarin users were included. In Latin American patients with AF.For the effectiveness outcomes,the use of DOACs compared with warfarin was significantly associated with decreased risks of SSE(HR=0.78;95%CI 0.64–0.96),stroke(HR=0.75; 95%CI 0.57-0.99),hemorrhagic stroke(HR=0.14;95%CI 0.05–0.36),all-cause death (HR=0.89; 95% CI 0.80–1.00),but not ischemic stroke,cardiovascular death.For the safety outcomes, compared with warfarin,the use of DOACs was associated with reduced risks of major or NMCR bleeding (HR=0.70; 95% CI 0.57–0.86),major bleeding (HR=0.70; 95%CI 0.53–0.92),ICH (HR=0.42; 95%CI 0.24–0.74),any bleeding (HR=0.70;95% CI 0.62–0.78), but not gastrointestinal bleeding. Conclusions: Current pooled data from the four post hoc analyses of RCTs suggested that compared with warfarin, DOACs appeared to have significant reductions in SSE,stroke,hemorrhagic stroke,all-cause death,major or NMCR bleeding,major bleeding,ICH and any bleeding, but comparable risks of ischemic stroke,cardiovascular death and gastrointestinal bleeding in Latin American AF patients.DOACs appeared to have significant reductions in SSE,hemorrhagic stroke,all-cause death,cardiovascular death,major or NMCR bleeding,major bleeding,ICH and any bleeding,increased the risk of myocardial infarction,but comparable risks of stroke,ischemic stroke and gastrointestinal bleeding in non-Latin American AF patients.